2020
DOI: 10.1111/all.14493
|View full text |Cite
|
Sign up to set email alerts
|

The neighbourhood natural environment is associated with asthma in children: A birth cohort study

Abstract: The human microbiome plays an important role in the development of allergic diseases and asthma. 1 According to the "biodiversity hypothesis," a lower exposure to the natural environment and biodiversity may adversely affect the human microbiome and its immunomodulatory capacity. 2 This hypothesis has been demonstrated in studies either showing lower microbiota diversity in the airways of children with asthma or finding a lower prevalence of atopic disease in children living the first years of their lives surr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 55 publications
(33 citation statements)
references
References 58 publications
1
31
0
1
Order By: Relevance
“…Some cross-sectional studies have reported positive associations between greenness exposure and asthma morbidity [ 7 , 8 , 9 ] both in children and in adults [ 10 ], whilst other studies have not confirmed these findings [ 11 , 12 ]. Inconsistent results were also reported from other studies with longitudinal design showing both harmful [ 13 , 14 ] and protective [ 15 ] effects of greenness on asthma. Indeed, only one cross-sectional study assessed the potential effect of urban greenness on asthma control reporting no significant effects [ 16 ].…”
Section: Introductionsupporting
confidence: 64%
“…Some cross-sectional studies have reported positive associations between greenness exposure and asthma morbidity [ 7 , 8 , 9 ] both in children and in adults [ 10 ], whilst other studies have not confirmed these findings [ 11 , 12 ]. Inconsistent results were also reported from other studies with longitudinal design showing both harmful [ 13 , 14 ] and protective [ 15 ] effects of greenness on asthma. Indeed, only one cross-sectional study assessed the potential effect of urban greenness on asthma control reporting no significant effects [ 16 ].…”
Section: Introductionsupporting
confidence: 64%
“…A longitudinal study conducted on 1050 children from a population‐based birth cohort recruited in Portugal showed that living in close proximity to a greener environment at birth had a protective effect on the development of allergic diseases and asthma at the age of 7. Conversely, living in neighbourhoods with a high number of fauna species appears to be associated with a higher risk of allergy, asthma and wheezing 120 …”
Section: Asthma and Environmental Sciencementioning
confidence: 97%
“…Research has shown that nature can provide many benefits for public health. Exposure to nature, particularly to public green and blue spaces, is associated with numerous health benefits including better cardiovascular and respiratory health ( Lane Kevin, 2017 , Cavaleiro Rufo, 2020 ), improved immune ( Cavaleiro Rufo, 2020 ) and cognitive function ( de Keijzer, 2018 ), and lower risk of disease ( Twohig-Bennett and Jones, 2018 ) and mortality ( Gascon, 2016 ). Although most of the research has focused on the physical health benefits of nature exposure, there is growing evidence showing that both physical and visual contact with nature is associated with better mental health outcomes ( Wendelboe-Nelson, 2019 ) such as lower levels of stress, anxiety ( Triguero-Mas, 2017 ) and rumination ( Bratman, 2015 ), reduced prevalence of somatization symptoms ( Triguero-Mas, 2017 ), improved biomarkers of stress ( Ribeiro, 2019 ), and overall better psychological well-being ( Pearson and Craig, 2014 ).…”
Section: Introductionmentioning
confidence: 99%